2020
DOI: 10.2147/rmhp.s241553
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hospital Characteristics Associated with Certified EHR Adoption among US Psychiatric Hospitals</p>

Abstract: Objective: The aim of this study was to explore the relationship between hospital characteristics and certified electronic health record (EHR) adoption in psychiatric hospitals in the US. Methods: Data were drawn from the American Hospital Association Annual Survey Database and the Centers for Medicare and Medicaid Services Hospital Compare data sets in 2016. Binary logistic regression analysis and χ 2 tests were performed to examine the relationship between certified EHR adoption and hospital characteristics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…To our knowledge it is the first qualitative study examining the perceptions of Swiss mental health specialists concerning EHR and their attitudes toward documenting mental health care in electronic medical records. As electronic documentation of mental health care raises ethical challenges worldwide, our findings are also relevant for other countries where EHR are widely implemented, such as North American and many European countries, [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 86%
“…To our knowledge it is the first qualitative study examining the perceptions of Swiss mental health specialists concerning EHR and their attitudes toward documenting mental health care in electronic medical records. As electronic documentation of mental health care raises ethical challenges worldwide, our findings are also relevant for other countries where EHR are widely implemented, such as North American and many European countries, [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 86%
“…Although the fraction of organizations failing to provide machine-readable data on standard charges was similar across hospital size, ownership, and system affiliation, nonprofit and system-member hospitals appear more responsive to the consumer-shoppable aspects of the rule. This may reflect greater adoption of commercially available, certified electronic health records among these two types of hospitals (Hu et al, 2020), as we found that consumer price comparison tools often were integrated with an electronic health record (e.g., provided through Epic’s MyChart functionality).…”
Section: Discussionmentioning
confidence: 94%
“…The study conducted by Adler-Milstein et al in the US between 2010 and 2015 found that 41.4% of all the hospitals operating throughout the country had basic EHR functions, 39.1% had comprehensive EHR functions, and 80.5% had at least one EHR function [ 39 ]. A study by Hu et al, which measured the stage of EHR adoption in psychiatric hospitals in the US in 2016, found the rate of hospitals with at least one EHR function to be 47.4% [ 27 ]. A similar study conducted by Liang et al in the US and China between 2007 and 2018 found the rate of hospitals with at least one EHR function to be 96% in the US and 85.3% in China [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that 47.4% of psychiatric hospitals holding EHR certificates in the USA have adopted the EHR. A link has been established between the 95% adoption of large hospitals and their certification [ 27 ].…”
Section: Introductionmentioning
confidence: 99%